Depression, anxiety, and stress among the community during COVID-19 lockdown in Saudi Arabia - Sulaiman A Alshammari; Razan Sultan Alotaibi; Ashwaq Ali Almajed; Thikrayat Abdulhafeeth Omar (Wolters Kluwer Medknow Publications, 2022)
Objectives: (1) We aimed to measure the levels of depression, anxiety, and stress among the Saudi population during COVID-19 lockdown and their association with different personal characteristics. (2) The secondary aims included assessing the perceived social and physical impacts of COVID-19 lockdown on individuals and the different coping strategy practices during this tough period. Methods: A cross-sectional study was conducted between May and June 2020 in Saudi Arabia. We collected data from both sexes aged 18 years and older using social media. The online questionnaire collected data on their sociodemographic, physical, and social conditions, and the presence and control of chronic diseases as well as their evaluation according to the Depression, Anxiety, and Stress Scale-21. Results: Of the 878 participants, 56.6% were female, 54.6% were aged between 35 and below, 52.6% were married, and 97.4% had a secondary school and above. Approximately a quarter of the participants or relatives had been diagnosed with COVID-19. Moderate-to-severe depression, anxiety, and stress were reported in 32.6%, 28.7%, and 22.6% of the participants, respectively. The younger than 35 years, unmarried, not working, and the previous diagnosis of COVID-19 were associated with higher scores of depression, anxiety, and stress. In addition, the participants reported several coping strategies such as doing physical exercise, hobbies, chatting over social media, watching TV/movies, playing electronic games, increasing religious prayers, and getting psychosocial help. Conclusion: A quarter of the participants reported a moderate-to-severe psychological impact. They adopted various strategies to reduce the adverse lockdown effect. In a future pandemic, health-care providers and policymakers can focus on potential risk factors and coping strategies to prevent, intervene early, and treat sufferers.